2019
DOI: 10.1108/intr-03-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with initial success versus failure in crowdfunding market

Abstract: Purpose Serial crowdfunding is becoming a common phenomenon as entrepreneurs repeatedly return to online crowdfunding to raise capital. In this study, the authors focus attention on serial crowdfunders, that is, entrepreneurs who experience launching more than one crowdfunding project. The purpose of this paper is to investigate the role of past experience on subsequent crowdfunding performance. This study also examines whether initial success vs initial failure leads serial crowdfunders to engage in more expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Maccani et al, 2017;Susha et al, 2015). Indeed, entrepreneurs are seen as innovators who generate new ideas and implement them (Lee and Chiravuri, 2019). Based on our review, we synthesized and identified the forms of uncertainty for our context.…”
Section: Uncertainty and Perceived Risk Perspectivementioning
confidence: 99%
“…Maccani et al, 2017;Susha et al, 2015). Indeed, entrepreneurs are seen as innovators who generate new ideas and implement them (Lee and Chiravuri, 2019). Based on our review, we synthesized and identified the forms of uncertainty for our context.…”
Section: Uncertainty and Perceived Risk Perspectivementioning
confidence: 99%
“…In a similar vein, entrepreneur characteristics have the potential to mitigate information asymmetry by signaling useful information about the quality of crowdfunding projects. The entrepreneurship literature stresses the importance of entrepreneur characteristics—such as gender, founding experience, social capital—as a key factor in predicting success or financial performance of new ventures (Kleinert & Mochkabadi, 2021; Lee & Chiravuri, 2019; Stuart & Abetti, 1990). Stuart and Abetti (1990) found evidence that the entrepreneurial experience, namely the number of past start‐up involvements, is one of the most significant antecedents contributing to a successful venture.…”
Section: Related Literature and Theoretical Backgroundmentioning
confidence: 99%
“…Like crowdfunding campaigns, ICOs cause low transaction costs, 1 have almost no documentation requirements but enable start-ups to raise substantial funds comparable to expensive and highly regulated venture capital transactions or IPOs (Chen 2018;Howell et al 2019). Moreover, ICOs, as well as crowdfunding campaigns, can overcome geographical barriers to funding and promote global dissemination at an early stage of the project as communication via the Internet is fast and cost-effective (Danmayr 2013; Lee Chang 2019). However, both crowdfunding campaigns and ICOs suffer from strong information asymmetry between emitters and investors (Albrecht et al 2020).…”
Section: Initial Coin Offeringsmentioning
confidence: 99%